Tracheal Length Measurement in Intubated Neonates to Guide the Design and Use of Endotracheal Tube Glottic Depth Markings - Jennifer B. Cerone; Joaquim M. B. Pinheiro (MDPI AG, 2022)
Background: Data on neonatal tracheal length are needed to inform the standardization of safety features for endotracheal tubes (ETTs) such as glottic depth markings. Laryngotracheal airway measurements are available from digital imaging in infants and children but not in neonates. We aimed to determine the tracheal length (TL) of intubated preterm and term neonates. Methods: An observational study was performed on 57 neonates of 22-42 weeks' gestation and <1 week of age. Two clinicians independently reviewed 153 digital chest radiographs to determine the carina position and TL. TL was measured from carina to mid-C4 (cricoid level). We analyzed interrater agreement (within 0.5 vertebral levels) on the position of the carina and TL. TL was plotted as a function of gestational age and weight, using graphical and regression analyses. Results: Carina position ranged from T3 to T5.5, with an interrater agreement of 95%. On image pairs concordant for carina position, TL determinations were virtually identical between readers (mean difference 0.1 mm, 95% CI −0.5-0.6 mm). Average mid-tracheal length overlies the body of T1. In infants aged less than 32 weeks' gestation, the mid-trachea lies <20 mm from the carina or the larynx. TL linearly correlates with gestational age, but correlation with birthweight best fits a segmented regression with a node at 1 kg. Conclusions: The functional length of the laryngotracheal airway can be reliably measured in sick neonates. It correlates well with gestational age and birthweight, and this information can inform the redesign of ETT markings to promote the safer use of these devices.